Factors Related to the Implementation of Facilitation Policies in the Prevention, Eradication, and Countermeasures of Narcotics Abuse and Illicit Trafficking (P4GN) by the North Sumatra Provincial National Narcotics Agency (BNN) - Lubis, Laniah; Hakin, Lukman; Sirait, Asima (PT FORMOSA CENDEKIA GLOBAL, 2024)
Effective policy implementation is crucial in combating drug abuse and trafficking, influenced by various complex factors beyond technical and administrative aspects. These factors include the policy's size and objectives, communication, resources, disposition, characteristics of implementing agents, and social conditions. This study, focused on the National Narcotics Agency (BNN) in North Sumatra Province, employs a cross-sectional design involving 70 respondents through total sampling. Using structured questionnaires, multivariate analysis identifies the policy’s size and objectives as significantly impactful, with a value of 12,821 times. In conclusion, refining and optimizing policy size and objectives, enhancing communication, ensuring resources, fostering positive dispositions, and aligning agents' characteristics with policy goals are recommended for effective implementation. Further research should explore specific optimization strategies and the dynamic interaction of factors in drug policy implementation.